Psychovegetative features at sick of the cirrhosis - L. P. Filippova; E. I. Beloborodova; Ye. V. Beloborodova; A. S. Alekseyeva; Ye. G. Shepeleva (Бюллетень сибирской медицины, 2011)
Complex kliniko-tool, laboratory, psychovegetative investigation of 139 various aetiologies sick by a cirrhosis (virus, alcoholic, mixed) is carried and severity levels on Childs-Pugh. The comparison group has been presented by 104 sick chronic hepatitises virus, alcoholic and mixed aetiologies. The control group included 30 healthy the person comparable floor and age. At sick of a cirrhosis, also as at sick of a chronic hepatitis, emotionally-labile, neurotic lines and high personal uneasiness prevailed. The tendency to sympathicotonia depended on weight of defeat of a liver. Prevalence of a tone and reactance of sympathetic department of vegetative nervous system is a compensatory strengthening of adaptive mechanisms.